Prediction Achievement and Simulated Decision Makers as an Extension of the Predictive Ability Criterion: Some Comments. - Salamon, Gerald L.; Uecker, Wilfred C.; Simmons, Richard (The Accounting Review, 1976)
The article presents comments of authors on the article "Prediction Achievement and Simulated Decision Makers As an Extension of the Predictive Ability Criterion," by Robert Libby published in the July 1975 issue of the periodical "The Accounting Review." Libby maintains that predictive ability is an inadequate information evaluation criterion because it does not consider explicitly the ability of the decision maker (DM) to utilize information. Libby argues that the prediction achievement index of the Brunswik Lens Model is a useful extension of the predictive ability criterion because it incorporates predictive ability as well as the DM's ability to utilize information. High prediction achievement demands not only high predictive ability, but correct utilization of information. Objectives of this comment are to identify those areas of accounting where prediction achievement is clearly an inappropriate index of usefulness and to question whether prediction achievement is an unqualified extension of predictive ability in any area accounting. The comment is organized around the two-part framework for the evaluation of accounting numbers used by the Committee on Asset Valuation Bases which originally proposed the use of the Brunswik Lens Model in the evaluation of accounting alternatives.